2007
DOI: 10.11606/issn.2176-7262.v40i4p493-499
|View full text |Cite
|
Sign up to set email alerts
|

Gangrena De Fournier

Abstract: RESUMO:A Gangrena de Fournier é uma grave infecção polimicrobiana que evolui com fasciite necrotizante, comprometendo principalmente as regiões genital, perineal e perianal. Caracteriza-se por rápida evolução e pode complicar com sepse, falência de múltiplos órgãos e óbito. A base do tratamento é o diagnóstico precoce e o desbridamento agressivo. Antibioticoterapia de amplo espectro, oxigenoterapia hiperbárica e cuidados locais são medidas complementares.Descritores: Gangrena de Fournier. Infecção. Fasciite Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
17

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 16 publications
0
14
0
17
Order By: Relevance
“…1,6,15,16 Although the majority of deceased patients had diabetes (4 out of 5), no significant correlation between diabetes as comorbidity and death was found.…”
Section: 6mentioning
confidence: 94%
“…1,6,15,16 Although the majority of deceased patients had diabetes (4 out of 5), no significant correlation between diabetes as comorbidity and death was found.…”
Section: 6mentioning
confidence: 94%
“…[23] Literature has shown that early surgical debridement is required in order establish antibiotic therapy, which aims to remove the devitalized tissue and stop the progression of infection. [29] The extent of necrotized tissue resection, performed in a surgery act, touches the viable tissue and may require additional procedures such as colostomies, indicated in situations where there is a risk for fecal contamination, and cystostomies, where the urine is considered an infection source. [14,26,27] Two studies, one Brazilian and one Spanish, have recommended as an adjunct therapy for treating Fournier's Gangrene, hyperbaric oxygen therapy, for increasing oxygen concentration in the tissues, fighting the anaerobic bacteria and promoting patient's healing.…”
Section: Therapeutic Modalities In Treating Fournier's Gangrenementioning
confidence: 99%
“…A desnutrição gerou impactos negativos na sobrevida dos pacientes. Outras doenças aparecem como fatores de risco, como hipertensão arterial, tabagismo, obesidade, linfomas 4,5 .…”
Section: Introductionunclassified
“…A exclusão de outras doenças também aumenta a suspeita clinica. Entre os diagnósticos diferenciais estão: celulite, hérnia estrangulada, abscesso de escroto, fasciite necrotizante estreptocócica ou estafilocócica, herpes simples, pioderma gangrenoso, necrose pelo warfarin, entre outros 5 .…”
Section: Introductionunclassified